THE DISTURBED GROUNDWATER LEVEL MODES OF CHORNOBYL AREA OF ALIENATION AND THEIR CONNECTION WITH VARIATIONS OF THE VOLUME ACTIVITY SR-90 - Shevchenko, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Results of water-balance and radiation-balance calculations, carried out by the data of hydro-geological observations enabled to evaluate the participation of regime factors and elements of balance in change concentration of 90Sr in groundwater and surface water.